Production of Biodiesel from Oleic Acid and Methanol by Reactive Distillation - Kusmiyati Kusmiyati; Agung Sugiharto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2010)
Biodiesel is an alternative diesel fuel that is produced from vegetable oils and animal fats. Generally, it is formed by transesterification reaction of triglycerides in the vegetable oil or animal fat with an alcohol. In this work, esterification reaction was carried out using oleic acid, methanol and sulphuric acid as a catalyst by reactive distillation method. In order to determine the best conditions for biodiesel production by reactive distillation, the experiments were carried out at different temperature (100 0C, 120 0C, 150 0C and 180 0C) using methanol/oleic acid molar ratios (1:1, 5:1, 6:1, 7:1, 8:1), catalyst/ oleic acid molar ratios (0.5%wt, 1%wt, 1.5%wt and 2%wt) and reaction times (15, 30, 45, 60, 75 and 90 minutes). Results at temperature 180 0C, methanol/ oleic acid molar ratio of 8:1, amount of catalyst 1% for 90 minute reaction time gives the highest conversion of oleic acid above 0.9571. Biodiesel product from oleic acid was analysed by ASTM (American Standard for Testing Material). The results show that the biodiesel produced has the quality required to be a diesel substitute. © 2010 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)